Pengaruh Profitability Terhadap Capital Buffer : Implikasi Terhadap Stabilitas Keuangan Bank Pada Tahun 2018-2021 - Juwinda Bokiu; Tri Anatasya Ardjun; Siti Yuliyani Mustapa (Peneliti.net, 2023)
This study aims to determine the influence of Profitability on Capital Buffer in Islamic Banking in Indonesia. The population of this study is Islamic banks in Indonesia for the 2018-2021 period, which is before and after the Covid-19 pandemic. The sample collection technique used in this study is purposive sampling technique. The number of companies sampled in this study is 6 (six) banks. The researchers used financial documents posted by each bank on its official website to generate secondary data, which they then compiled. Capital Buffer at Indonesian Sharia Commercial Banks experienced an impact of 88% from 2018 to 2021. The results of the hypothesis test clearly show that Profitability has a positive and significant influence on Capital Buffer or BOPO. Therefore, the higher the Capital Buffer, the greater the bank's ability to bear the risk of any risky credit or productive assets.